Alterações hematológicas e histopatológicas em pacu, Piaractus mesopotamicus Holmberg, 1887 (Osteichthyes, Characidae), tratado com sulfato de cobre (CuSo4) - Tavares-Dias, Marcos [UNESP]; Martins, Maurício Laterça [UNESP]; Canello Schalch, Sérgio Henrique [UNESP]; Onaka, Eduardo Makoto [UNESP]; Flores Quintana, Carolina Isabel [UNESP]; De Moraes, Julieta Rodini Engrácia [UNESP]; De Moraes, Flávio Ruas [UNESP] (My University, 2002)
This paper evaluated the haematological and glycaemic parameters in Piaractus mesopotamicus (Osteichthyes, Characidae) infected with Monogenea Anacanthorus penilabiatus Boeger, Husak & Martins, 1995 (Dactylogyridae) after treatment with 0.50 mg/L and 1.00 mg/L of copper sulphate (CuSO4). The efficacy of the CuSO4 was observed in the first day after administration but not after eight, fifteen or thirty days. The histopathological analyses showed hyperplasia of the epithelium and circulatory changes in the gills. In the first day after treatment significant changes (P<0.05) in the total count of erythrocyte, leucocyte, mean corpuscular haemoglobin concentration (MCHC) were observed. The fishes treated with 0.50 mg/L showed decrease in the haemoglobin levels and in the percentage of neutrophils (P<0.05). The dose of 1.00 mg/L provoked increase of glycaemia but reduction in the lymphocytes percentage when compared with 0.50 mg/L in the 8th day. Fifteen days after 1.00 mg/L treatment, values of mean corpuscular volume (MCV) and special granulocitic cells (S.G.C.) percentage decreased. Nevertheless, increase of total leucocyte number was observed. Thirty days after treatment with 0.50 mg/L showed increased S.G.C. and treatment with 1.00 mg/L showed increased lymphocyte.
Hematological and histopathological alteration in pacu Piaractus mesopotamicus Holmberg, 1887 (Osteichthyes, Characidae) after treatment with copper sulphate (CuSO4)
Keywords: Copper sulphate; Freshwater fish; Glycaemia; Haematology; Histopathology; Piaractus mesopotamicus; copper sulfate; glucose; hemoglobin; analysis; animal experiment; controlled study; drug efficacy; epithelium; erythrocyte count; fish; gill; glucose blood level; granulocyte; hematological parameters; hemoglobin determination; histopathology; hyperglycemia; hyperplasia; infection; leukocyte count; lymphocyte; mean corpuscular hemoglobin; mean corpuscular volume; neutrophil; nonhuman; observation; systemic circulation; Animalia; Characidae; Dactylogyridae; Monogenea; Osteichthyes; Piaractus; Pisces